(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
English literacy is a foundational competency for global participation, yet students in Maluku continue to demonstrate low literacy levels due to geographical isolation, limited educational infrastructure, and the absence of culturally relevant instructional materials, resulting in learning that feels disconnected from students’ daily lives and local identity. This study examines the impact of CTL-based English teaching materials embedded with Maluku cultural content on empowering junior high school students’ literacy skills. Unlike previous studies that focused on general CTL application, this study uniquely integrates Maluku local cultural content, specifically Hena Puan culture, into EFL materials for Islamic junior high school students in an archipelagic region with limited educational resources. A pre-test-post-test control group experimental design was employed involving 60 students from MTs Muhammadiyah Nusa Puan. Data were analysed using descriptive statistics and independent samples t-test. Findings revealed a significant improvement in the experimental group’s mean score (52.23 to 79.43) compared to the control group (52.93 to 76.40), significance value 0.000 (<0.05). These findings suggest that culturally embedded materials increase student engagement and contextual relevance, accelerating literacy development. This study carries both theoretical and practical implications for enhancing English literacy outcomes and sustaining local cultural identity.